2022
DOI: 10.7150/ijbs.67974
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-COX2 inhibits Fibroblast Activation and Epidural Fibrosis by Targeting EGR1

Abstract: Rationale: Epidural fibrosis is one of the contributors to failed back surgery syndrome (FBSS) with a high incidence of about 80,000 cases per year. The fibrosis spreads from the operative region to the dura mater or the nerve root and results in functional incapacity and pain after laminectomy. Our previous study showed that down-regulation of lncRNA-COX2 is involved in the epidural scar formation. However, it remains unknown whether lncRNA-COX2 participate in the fibroblast activation and epidural fibrogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Wu et al indicated that Egr1 is essential for myofibroblast transdifferentiation and the wound healing process [ 72 ]. An in vitro study demonstrated that the lncRNA COX prevents aberrant epidural fibrosis by targeting Egr1 [ 73 ]. TGF-β is a major factor driving fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al indicated that Egr1 is essential for myofibroblast transdifferentiation and the wound healing process [ 72 ]. An in vitro study demonstrated that the lncRNA COX prevents aberrant epidural fibrosis by targeting Egr1 [ 73 ]. TGF-β is a major factor driving fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of epidural fibrosis has been reported in FBSS patients in former research ( Bosscher and Heavner, 2010 ; Lin et al, 2019 ). It occurs as a conglomerate of fibrotic tissue, surrounding lateral nerve roots and contributing to nerve root entrapment ( Sebaaly et al, 2018 ; Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive scar tissue may invade the spinal canal causing mechanical compression of nerve roots after laminectomy and spinal surgery, and it may also cause post-laminectomy epidural adhesion to the dura mater. These changes may lead to chronic back pain and functional incapacity and increase the risks of complications during revision surgery [ 24 ].…”
Section: Pathogenesis Of Cpssmentioning
confidence: 99%
“…In some chronic pain patients, opioids are often the only analgesic that can help to relieve pain. However, the aforementioned systematic review reported that approximately 80% of patients experienced at least one major side effect, with constipation (41%), nausea (32%), and somnolence (29%) being the most common ones [ 24 ]. In addition, opioids are highly addictive and susceptible to abuse, and more than half of regular opioid users still suffer significant low back pain and radicular pain [ 85 ].…”
Section: Current Treatment Of Cpssmentioning
confidence: 99%
See 1 more Smart Citation